Water Saver Heroes: Community Solutions for Clean Water and Sustainable Sanitation in Loa Ulung Village - Nurfadilla; Arya Yuliansyah Putra; Hazizah Tausia Abdania; Yerita Adellia; Nadya Zahira Shafa; Diva Nabilah Anggraeni; Rahmi Susanti (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Access to clean water and adequate sanitation practices are essential in preventing environment-related diseases. However, awareness among communities in rural regarding water quality remains limited. Therefore, community-based interventions are needed to improve clean water literacy and healthy sanitation behaviors in Loa Ulung Village, Kutai Kartanegara, East Kalimantan. Objective : The Water Saver Heroes program aims to increase community knowledge and skills regarding clean water criteria and the application of simple water filtration technologies using local materials. This program also encourages young people to play role as agents of sustainable education. Research Methods/ Implementation Methods : The method used was a pre-post test design inlving 27 participants. Participants received instruction through interactive lectures, demonstrations on making simple water filters, group discussions, and educational media. Changes in participants' understanding were evaluated using the Wilcoxon Signed Rank Test to measure the effectiveness of the education. Results : No participants had a decrease in their scores. There were 26 participants whose scores increased in knowledge (mean rank = 13.50, total ranking = 351.00), and 1 participant did not experience any change. These findings indicate that the education provided was successful in improving participants' understanding of the importance of clean water and how to make water filters. Conclusion/Lesson Learned : The Water Saver Heroes program has proven effective in increasing community knowledge, skills, and awareness about clean water and sanitation. In addition, this program demonstrates the important role of youth as agents of sustainable change in the community, who can serve as models for similar programs in other areas.